2019
DOI: 10.12691/education-7-11-8
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Industrial Internship for Vocational School of Mechanical Engineering in Tegal

Abstract: This research aims to evaluate the implementation of industrial internship program on the aspects of: 1) planning, 2) process, and 3) results. In this study, the industrial internship is for the students of Vocational High School in Mechanical Engineering program. This research is a quantitative research with the respondents of teachers, students, and the industries in Tegal regency. The location of this research is in three Vocational High School (VHS) with an engineering program and the industries for studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Based on these data it can be concluded that the purpose of vocational education that prepares students to be ready to work after graduation is interpreted as not optimal. In addition, there is a mismatch between vocational education competencies and those needed by the world of work, so to be able to align these competencies with the industry needs to involve the industry in implementing learning programs (Fakhri & Munadi, 2019). Learning in vocational high schools should emphasize the psychomotor aspects of students because by strengthening these aspects students will get real experiences with what they understand.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these data it can be concluded that the purpose of vocational education that prepares students to be ready to work after graduation is interpreted as not optimal. In addition, there is a mismatch between vocational education competencies and those needed by the world of work, so to be able to align these competencies with the industry needs to involve the industry in implementing learning programs (Fakhri & Munadi, 2019). Learning in vocational high schools should emphasize the psychomotor aspects of students because by strengthening these aspects students will get real experiences with what they understand.…”
Section: Introductionmentioning
confidence: 99%